Improvement of Strength and Radiation Protection Properties of Biodegradable Jute Fiber Reinforced Material - Verma, S.; Amritphale, S.S.; Das, S. (Проблемы прочности, 2017)
Over past few years, polymer composites with natural fiber reinforcement, called eco-composites, have achieved a worldwide compliance due to their strong potentiality to save the environment from pollution as a result of their ultimate disposability, as compared to glass-filled composites. Since natural fibers combine a low cost and low density with high toughness, biodegradability, renewability, reduced tool wear, and higher energy recovery. They are carbon dioxide neutral when burned and are present in abundance, which make composites made from them also sustainable and economical. We report a facile method for the improvement of strength and radiation protection properties of biodegradable jute fiber reinforced material by ceramic treatment of red mud. The developed powder was further blended with polyester resin to form thick, viscous radiation protection organic gel-based material. The developed protection gel material was then cured for making advanced non-toxic, biodegradable radiation protection panels using jute as natural fiber reinforcement. The developed radiation protection panels were analyzed by X-ray method with different energies of X-ray photons found to possess highly competent properties. Their various mechanical properties, like tensile, flexural, and impact strength values and morphological features were evaluated. The developed non-toxic, biodegradable, jute fiber reinforced, X-ray radiation protection panels combine good shielding and mechanical properties, which ensures their broad application spectrum ranging from diagnostic X-ray and CT scanner room installations to nuclear power plant and other strategic radiation shielding tasks.